2021
DOI: 10.1007/s00348-021-03178-8
|View full text |Cite
|
Sign up to set email alerts
|

A novel single-camera approach to large-scale, three-dimensional particle tracking based on glare-point spacing

Abstract: A novel method for three-dimensional particle tracking velocimetry (PTV) is proposed that enables flow measurements in large volumes [ V = O(10 m 3 )] using a single camera. Flow is seeded with centimeter-sized soap bubbles, when combined with suitable illumination, produce multiple glare points. The spacing between the two brightest glare points for each bubble is then utilized to reconstruct its depth. While the use of large soap bubbles comes at the expense of non-Stokesian behaviour, the excellent ray opti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 28 publications
(31 reference statements)
0
9
0
Order By: Relevance
“…Given that D B is known, the distance (depth o) of the bubble from the camera plane could then be estimated from a single perspective by evaluating the features of the glare-point pattern in the bubble image. Thus, Hou et al (2021) demonstrated the principle successfully in a very large volume of order (V = O(10 m 3 )).…”
Section: Introductionmentioning
confidence: 91%
See 3 more Smart Citations
“…Given that D B is known, the distance (depth o) of the bubble from the camera plane could then be estimated from a single perspective by evaluating the features of the glare-point pattern in the bubble image. Thus, Hou et al (2021) demonstrated the principle successfully in a very large volume of order (V = O(10 m 3 )).…”
Section: Introductionmentioning
confidence: 91%
“…Note that any error of D B linearly propagates to the depth estimate. Hou et al (2021) used a second camera perspective in order to The experiment was performed in a room without any external airflow. The bubbles were guided through a 1 m-long acrylic-glass tube, illuminated by a diffuse LED screen providing homogeneous illumination over a 20 cm × 10 cm area, and recorded via a high-speed camera (Photron Fastcam Mini WX100, 2048 × 2048 px 2 , f = 100 mm, N = 11).…”
Section: Tracer Sizementioning
confidence: 99%
See 2 more Smart Citations
“…Suppose the target microbubbles are spherical particles, in-focus bright spots namely the glare points will appear 26 , 27 . Here, we analyze the glare points of target microbubbles under an observation of 90 deg for underwater microbubbles detection and identification method.…”
Section: Underwater Microbubbles Detection and Identification Based O...mentioning
confidence: 99%